Analysis of Higher Order Thinking Skills on End of Year Assessment Questions for Islamic Education Subjects - Shinta Sri Pillawaty; Nurhamzah Nurhamzah; Nina Nurmila (Jurnal al-Thullab, 2022)
The Higher Order Thinking Skills analysis on the final year assessment questions for the subject of Islamic Religious Education will illustrate the results of the comparison of questions that have the character of critical thinking and questions that do not have a stimulus for critical thinking. This research method uses a qualitative research method that is descriptive document analysis. This study aims to describe questions based on the level of thinking, namely grouping questions into the categories of Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and High Order Thinking Skills (HOTS), and grouping questions based on the type of stimulus used as the basis for the questions. In obtaining data related to assessment questions, the results show that out of Year-End Assessment questions on Islamic Religious Education Subjects found 29% HOTS questions (Higher Order Thinking Skills), 31% about MOTS (Middle Order Thinking Skills) and 40% about LOTS (Lower Order Thinking Skills). In the form of HOTS questions, there is actual, factual, conceptual and procedural material stimulus. The types of stimulus contained in the problem are discourse, pictures and fragments of cases. The stimulus contained in the High Order Thinking Skills (HOTS) questions is presented in the form of discourse. Analisis Higher Order Thinking Skills pada soal penilaian akhir tahun mata pelajaran Pendidikan Agama Islam ini akan menggambarkan hasil perbandingan soal yang memiliki karakter berpikir kritis dan soal yang tidak memiliki stimulus untuk berpikir kritis. Metode penelitian ini menggunakan metode penelitian kualitatif yang bersifat deskriptif analisis dokumen. Penelitian ini bertujuan mendeskripsikan soal berdasarkan tingkat berpikir, yaitu mengelompokkan soal dengan kategori Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), dan High Order Thinking Skills (HOTS), serta mengelompokkan soal berdasarkan jenis stimulus yang digunakan sebagai dasar pertanyaan. Dalam memperoleh data yang terkait dengan soal menunjukkan hasil bahwa Penilaian Akhir Tahun pada Mata Pelajaran Pendidikan Agama Islam ditemukan 29% soal HOTS (Higher Order Thinking Skills), 31% soal MOTS (Middle Order Thinking Skills) dan 40% soal LOTS (Lower Order Thinking Skills). Dalam bentuk soal HOTS memiliki stimulus materi yang aktual, faktual, konseptual dan prosedural. Jenis stimulus yang terdapat dalam soal yaitu wacana, gambar dan penggalan kasus. Stimulus yang terdapat dalam soal High Order Thinking Skills (HOTS) disajikan dalam bentuk wacana.